A preliminary estimate of the economic impact of long COVID in the United States. Issue 4 (2nd October 2022) - Mirin, Arthur A.
ABSTRACT: Post-Acute Sequelae of SARS CoV-2 infection (PASC), more commonly referred to as Long COVID, is one of the most daunting health-care grand challenges facing the United States today. Affecting millions of Americans, Long COVID extracts a huge cost both socially and economically. In this article, we provide a preliminary estimate of the annual income loss and medical costs due to Long COVID in the United States. With many Long COVID patients either meeting the diagnostic criteria for myalgic encephalomyelitis / chronic fatigue syndrome (ME/CFS) or exhibiting symptoms consistent with ME/CFS, we utilize ME/CFS to help guide our estimates. Based on the nearly 86 million documented US COVID survivors as of June 25, 2022, and considering a range of 5% to 20% of those survivors currently afflicted with Long COVID, we estimate annual medical costs to range from 43 billion to 172 billion, and lost income to range from 101 billion to 430 billion. This corresponds to an annual economic impact (exclusive of costs of disability services, social services, and lost income on the part of caretakers) ranging from roughly 140 billion to 600 billion.